PERSPECTIVES OF PHYSICAL THERAPISTS TOWARDS THE USE OF SMARTPHONE APPLICATIONS FOR PATIENT’S REHABILITATION (The Research of Medical Science Review, 2025)
Background: Smartphone applications have emerged as powerful tools in the realm of physical therapy, by empowering both patients and healthcare providers. The study will delve into the potential advantages of smartphone applications in physical therapy including home-exercise programs, progress tracking, monitoring, education, and self-management.Methodology: A cross-sectional survey was conducted among 232 physical therapists. The informed consent was taken from each participant for the data collection process. The data was analyzed through Statistical Package for the Social Science (SPSS) version 22.0 and presented the results in the form of Descriptive statistics.Results: The results are revealing that only half were aware of these applications and had them installed on their devices. Most respondents supported the development of more apps for education in clinical practices, while a smaller percentage expressed a negative stance. Most participants found smartphone apps useful for guiding patients about home-exercise plans, and 50.9% believed that physical therapists should explain to patients when they wish to use these apps during consultations.Conclusion: The study concludes that physical therapy-related smartphone applications must be more widely used and understood by physical therapists to enhance their clinical decision-making processes. Factors such as time constraints and the patient-therapist trust relationship influence the adoption or rejection of these applications during consultations. It has revealed a significant gap in the knowledge and utilization of these applications among physical therapists